X/2+x/3=4 4-x/7=x/9 7+x/10=x+9/5 3(x-3)=x+2(x+5) -4(x+2)+3(x-1)-2...

X/2+x/3=4 4-x/7=x/9 7+x/10=x+9/5 3(x-3)=x+2(x+5) -4(x+2)+3(x-1)-2=4(x-2)+9
Гость
Ответ(ы) на вопрос:
Гость
1) (3х+2х)/6=4 3х+2х=4*6 5х=24 х=24/5 х=4 4/5 2) х/9-х/7=4 (7х-9х)/63=4 -2х=4*63 -2х=252 х= -126 3) х-х/10=7-9/5 (10х-х)/10=35/5-9/5 9х/10=26/5 9х=26/5*10 9х=52 х=52/9 х=5 7/9 4) 3х-9=х+2х+10 3х-3х=10+9 0≠19 - уравнение не имеет смысла 5) -4х-8+3х-3-2=4х-8+9 -х-4х=1+8+5 -5х=14 х= -14/5 х= -2 4/5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы